Predicting Long-Term Mortality, Morbidity, and Survival Outcomes Following a Cardiac Event: A Cardiac Rehabilitation Study. (February 2019) - Graham, Helen L; Lac, Andrew; Lee, Haeok; Benton, Melissa J
Background: Cardiac rehabilitation (CR) has been shown to decrease mortality and morbidity but estimations vary. While there is significant literature supporting short-term benefits, there is not a similarly body of research as to long-term (LT) benefits. Low participation rates in CR are due to several causes and evidence demonstrating positive LT outcomes could be a catalyst to increased participation rates. Objective: To predict LT mortality, readmission, and survival benefits associated with CR participation in a nationally certified program. Methods: Investigators collected mortality and hospital readmission data in a retrospective study to examine a cohort of cardiac patients following a myocardial infarction (MI), MI/percutaneous coronary intervention (PCI), and coronary artery bypass graft (CABG) up to 14 years ago. Hospital electronic medical record (EMR; n = 207) were used to measure hospital readmission outcome and State Health Department records (n = 361) for mortality and survival outcomes. Participation in CR, age, gender prior history of cardiac event, and diagnosis were used to predict readmission, mortality, and survival. Results: Approximately half (52.1%) the sample participated in CR. Participants included 72% males, average age 68 years (38-91 years), and were predominantly Non-Hispanic white. CR participants attended an average of 20 sessions. CR group differed in diagnoses MI (58.5%), CABG (57.4%) and in prior history of heart disease (25.4%) from the non-cardiac rehabilitation (NCR) group (83.2%, 25.4%, 42.2%, respectively) ( P < .05). After controlling for the covariates in logistic regression analyses, the CR group independently predicted lower all-cause mortality (odds ratio, OR = 0.22, 95% CI 0.12 to 0.39) and decreased hospital readmissions (OR = 0.48, 95% CI 0.24 to 0.96). After controlling for the covariates in survival analysis, the CR group significantly contributed to decreased likelihood of death hazard (hazard ratio = 0.36, 95% CI 0.24 to 0.54). Median survivor time for the participants was 5.91 years, SD = 3.81 years. Conclusions: Participation in CR for middle age and elderly patients is associated with increased survival, a marked decrease in all-cause mortality, and a decrease in cardiovascular-related hospital readmission. A referral to a nationally certified outpatient CR program prior to hospital discharge and early enrollment may improve LT outcomes.